Synthesis, Growth and characterization of semi-organic zinc (tris) thiourea chloride crystal - V, Revathi; Rajendran, V (Recent Research in Science and Technology, 2012)
<!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-ansi-language:#0400; mso-fareast-language:#0400; mso-bidi-language:#0400;} --> <!--[endif] --> Zinc (Tris) Thiourea chloride (ZTTC) a semi organic nonlinear optical material has been grown by slow evaporation process from its aqueous solution. The grown crystals were subjected to characterize by Single crystal X-ray diffraction, Powder X-ray diffraction, Fourier transform infrared spectroscopy, optical transmission spectrum and Dielectric studies. Single crystal X-ray diffraction studies confirm the orthorhombic structure. The FTIR spectrum analysis has confirmed the functional groups in the ZTTC. Its optical behavior was examined by UV-Vis and found that the crystal is transparent in the region between 841-2000 nm. Dielectric study shows that the dielectric constant decreases with increase in frequency.